Pregnancy in autoimmune rheumatic diseases - Tincani, Angela (Henry Stewart Talks, 2007)
Pregnancy and the immune system, SLE flares during pregnancy, Gestational outcome in SLE, Predictors of obstetrical and neonatal complications in SLE, Autoantibodies that can affect pregnancy outcome: antiphospholipid antibodies, Obstetrical complications and newborns outcome in antiphospholipid syndrome, Autoantibodies that can affect pregnancy outcome: anti-Ro/SS-A antibodies, Neonatal lupus, Congenital heart block and in utero exposure to dexamethasone
Archived at 2018/05/31